2009
DOI: 10.2215/cjn.02260409
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and the Cardiovascular System

Abstract: Several epidemiologic and clinical studies have suggested that there is a strong association between hypovitaminosis D and cardiovascular disease (CVD). Hypovitaminosis D was reported as a risk factor for increased cardiovascular events among 1739 adult participants in the Framingham Offspring Study. Analysis of more than 13,000 adults in the Third National Health and Nutrition Examination Survey (NHANES III) showed that even though hypovitaminosis D is associated with an increased prevalence of CVD risk facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
136
1
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(149 citation statements)
references
References 61 publications
(39 reference statements)
3
136
1
9
Order By: Relevance
“…A prospective association between reduced levels of 25-OH-vitamin D and cardiovascular risk has been observed 23,24) ; however, in a study of African Americans with type 2 diabetes mellitus, 25-OH-vitamin D levels correlated with increased calcified plaque in the aorta and carotids 52) . Thus, concern has been expressed that vitamin D could potentially accelerate vascular disease.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A prospective association between reduced levels of 25-OH-vitamin D and cardiovascular risk has been observed 23,24) ; however, in a study of African Americans with type 2 diabetes mellitus, 25-OH-vitamin D levels correlated with increased calcified plaque in the aorta and carotids 52) . Thus, concern has been expressed that vitamin D could potentially accelerate vascular disease.…”
Section: Resultsmentioning
confidence: 99%
“…Vitamin D insufficiency (25-OH-vitamin D <30 ng/mL) 20) is relatively common in postmenopausal women 21,22) , and recent studies have suggested an association between reduced levels of vitamin D and cardiovascular risk 23,24) . Multiple mechanisms have been proposed to explain the deleterious role of hypovitaminosis D on cardiovascular risk 24) , including the negative correlation between serum vitamin D levels and arterial stiffness 25,26) .…”
Section: Clinical Evaluation and Bone Mineral Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiologic data demonstrated that the rate of diseases such as coronary heart disease, hypertension, and diabetes increase as we move away from the equatorial region, which is related to vitamin D or the lack of it. Low serum vitamin D levels were observed in patients with myocardial infarction, stroke, heart failure, diabetic cardiovascular disease, and peripheral arterial disease (11)(12)(13). Therefore, low vitamin D levels could affect as a reason or a result for acute liver injuries.…”
Section: Discussionmentioning
confidence: 99%
“…In another recent comprehensive study, vitamin D deficiency is reported to be associated with hypertension, high blood glucose, cardiovascular diseases and metabolic syndrome (2). Again, in a study by Wang et al (3) it has been reported that in the cases in which the serum 25-hydroxy vitamin D (25-OHD) level was lower than 15 ng/mL, the risk for initial onset of cardiovascular system problem was found to be higher (at least two-fold) than the control group (serum 25-OHD >15 ng/mL).…”
Section: Introductionmentioning
confidence: 99%